Improving the data quality of Advanced LIGO based on early engineering run results. (1st December 2015) - Nuttall, L K; Massinger, T J; Areeda, J; Betzwieser, J; Dwyer, S; Effler, A; Fisher, R P; Fritschel, P; Kissel, J S; Lundgren, A P; Macleod, D M; Martynov, D; et al.
Abstract: The Advanced Laser Interferometer Gravitational-wave Observatory (LIGO) detectors have completed their initial upgrade phase and will enter the first observing run in late 2015, with detector sensitivity expected to improve in future runs. Through the combined efforts of on-site commissioners and the Detector Characterization Group of the LIGO Scientific Collaboration, interferometer performance, in terms of data quality, at both LIGO observatories has vastly improved from the start of commissioning efforts to present. Advanced LIGO has already surpassed Enhanced LIGO in sensitivity, and the rate of noise transients, which would negatively impact astrophysical searches, has improved. Here we give details of some of the work which has taken place to better the quality of the LIGO data ahead of the first observing run.